The reconstructive-restorative intervention at dermoid cyst complicated of multiple fistulas and abscesses of area perianal - Mikhalchenko, O. I.; Leonov, I. O. (Modern medical technology, 2019)
Theclinical case ofreconstructiveintervention performed on dermoid cyst complicated of multiple fistulas of area perianal is presented. An operation was performed: excision the cyst with fistulas and followed plastic restore its own tissues.